Pengaruh Kompetensi dan Kompensasi terhadap Kepuasan Kerja dan Kinerja Pegawai (Studi Kasus Pada Dinas Kelautan dan Perikanan Kabupaten Kepulauan Sangihe ) - Rudlia, Justisia Iriani (Universitas Sam Ratulangi, 2016)
The purpose of this study was to see wether there is an influence of competency and compensation on job satisfaction and employee performance at Department of Marine and Fisheries of Sangihe Islands Regency.Data Analysis method using path analysis with SPSS 22.0. The result showed that competency not significant effect on job satisfaction but significantly effect on employee performance. The result also showed that compensation significantly effect on job satisfaction but,not significant effect on employee performance and job satisfaction significantly effect on employee performance. Keywords : competencies, compensation, work satisfaction, employee performance